Water and sediment quality of Rajang River at Pelagus area, Sarawak - Phan, Tze Pei (Universiti Malaysia Sarawak (UNIMAS), 2015)
This study was carried out to examine the water and sediment quality of Rajang River at Pelagus area to produce a baseline reference of the environment before the construction of a hydroelectric power dam that has been scheduled in the development plan of Sarawak. Samples were collected at 12 stations along the Rajang River from Pelagus Rapid to Punan Bah on 27th to 28th August 2014 and 14th to 15th January 2015. Results of this study show that water quality was affected by logging, vegetation and waste from households and animals around the study area. The total suspended solids and turbidity of stations 1, 5, 6, 7, 10, 11 and 12 exceeded Class II limit of 50 mg/L while dissolved oxygen of stations 1, 6 and 11 fall into Class III (3 – 5 mg/L) based on INWQS. Biochemical oxygen demand of stations 1, 2, 4, 5, 6, 7, 8, 9, 10, 11 and 12 are not complied with Class II (1 – 3 mg/L) while chemical oxygen demand of all the stations are exceeded Class II limit 25 mg/L based on INWQS. Moreover, total ammonia nitrogen of all the stations except station 8 exceeded Class II limit of 0.3 mg/L According WQI, only stations 2, 3, and 4 which are tributaries are classified under Class II (76.5 – 92.7) while stations 1, 6, 7 and 11 that are located at main river and other stations 5, 8, 9, 10 and 12 which are located at tributaries are not compliance with Class II. WQI of station 7 – 12 which are more nearer to the Bakun Dam are classified in Class III as the chemical oxygen demand and biochemical oxygen demand of them are higher than others. Dissolved oxygen, turbidity, total suspended solids and total sulphide of most of the stations that located at main river are higher than stations at tributaries. Sediment samples are mineral acidic and higher organic matter has recorded with higher weight of water content whereas the total phosphorus and total nitrogen in sediment are 46.53 – 102.86 mg/kg and 0.73 – 6.17 mg/kg.